Successful coaching - Martens, Rainer 1942- (Human Kinetics, 2024)
"This book is a practical guide to effectively handling the duties and expectations involved in coaching scholastic and club athletes and teams. It details how coaches can develop coaching philosophies, objectives, and leadership styles to become strong decision makers and communicators as well as how to use discipline and the creation of a culture of character to motivate athletes and support their maturation, cultural uniqueness, mental health, and well-being. It also describes how to be an organized and skillful team manager and teacher capable of enhancing athletes' skills and knowledge to meet the physical and mental demands of the sport and educating athletes about healthy nutrition and the dangers of drugs and alcohol to enhance their sport-specific performance and general health"--
Keywords: School sports / Coaching / United States; Sports scolaires / Entraînement / États-Unis; School sports / Coaching; United States